The Dynamics of Life Insurance Demand: Insights from Butwal Sub-Metropolitan City - Bhandari, Naba Raj; Sapkota, Suresh (Journal of Interdisciplinary Studies, 2024)
This study aims to investigate the factors contributing to life insurance policy demand in this dynamic business scenario. The study identifies key variables, including demographic factors, economic factors, perceived service of insurance companies, company image, other insured and peer influence, and various motives of individuals as major explanatory factors of life insurance demand. The findings and conclusions are derived from a descriptive and causal-comparative study methodology that is survey-based. A comprehensive survey was performed among the residents of Butwal Sub-Metropolitan city. Considering the total number of insured residing in the Butwal Sub-metropolitan City population, 420 individuals purchased life insurance policies from the insurance company branch office located in Butwal, Sub-metropolitan city, was taken as a sample and approached through the help of the corresponding insurance company’s insurance agents. The study employed inferential statistical techniques to examine the strength of the explanatory variables in explaining the demand for life insurance. The study’s result revealed that economic factors, insurance service perception, insurance awareness, persuasion and influence, tax-saving motives, bequest motives and wealth accumulation motives are the most significant factors in explaining the life insurance demand. It is found from the Kruskal Wallis test that the number of dependent family members of respondents has a significant difference in the demand for life insurance. As a way to better meet customer needs and increase the total demand for life insurance policies in this dynamic business environment, insurance companies can use the study’s insightful findings to customize their offerings and marketing plans.